Answer:
![y = (2)/(3) x - 3 (2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/hjhiwuvumd27y0pi1xa2ns4x2uuip8r0ak.png)
Explanation:
Let's rewrite the given equation in the form of y= mx +c, where m is the gradient while c is the y-intercept.
2x -3y= 9
3y= 2x -9
Divide by 3 throughout:
![y = (2)/(3) x - 3](https://img.qammunity.org/2021/formulas/mathematics/college/keiny1i45xphjycss3qhclv5wpwxme5q38.png)
Thus, the gradient of given line is ⅔.
Parallel lines have the same gradient.
Therefore, gradient of line is ⅔.
Substitute m=⅔ into the equation:
![y = (2)/(3) x + c](https://img.qammunity.org/2021/formulas/mathematics/college/hq4838bloq7nr91022gr6peb7coeorcbve.png)
To find the value of c, substitute a pair of coordinates.
When x=4, y= -1,
![- 1= (2)/(3) (4) + c \\ - 1 = (8)/(3) + c \\ c = - 1 - (8)/(3) \\ c = - 3 (2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/t5p5iwagoitbnjuwjeuza9ztfbtexlkqfl.png)
Substitute the value of c:
![y = (2)/( 3) x - 3 (2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/college/is6feci68yg5b9kqow3a5xprlcc8gm1mdl.png)